Pengaruh Keterampilan Attending Guru Terhadap Keterbukaan Siswa dalam Konseling Individu - Lase, Aloysius Putrawan; Munthe, Mondang (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to determine the effect of attending skills of Guidance and Counseling teachers on student openness to participate in individual counseling service activities at SMP Negeri 1 Idanogawo. The results showed that there was a positive relationship and significance in the attending variable of BK teachers (X) to the variable of student openness (Y) class VIII – A at SMP Negeri 1 Idanogawo. Based on data analysis, it is known that the results of research data analysis confirmed that there is an influence of attending BK teachers on student openness and the contribution of variable X to Y is 41.0%, meaning that the influence of attending BK teachers on the openness of grade VIII – A students at SMP Negeri 1 Idanogawo. And the remaining 59% are subjects that affect openness that are not included in the research studied